Industrial Toxicants in Bangladesh: Sources, Exposure and Public Health Impacts – A Systematic Review: Sources, Exposure and Public Health Impacts – A Systematic Review: Industrial Toxicants in Bangladesh: Sources, Exposure and Public Health Impacts – A Systematic Review - Niloy, Lamiya Tasnim; Hossain, Irin; Abbas, Md Golam; Sattar, Shahria; Naznnen, Afsana; Foyzunnahar, Mst; Mujib, Hazzaz Bin; Tabassum, Aurpa; Alam, Nusrat-E-; Yeasmin, Sanzidah; Sifat, Anjum Ara; Jahan, Nelema; et al. (Journal of the Medical College for Women & Hospital, 2025)
Background: Bangladesh’s rapid industrialization has significantly contributed to economic growth but has also resulted in widespread environmental contamination. Industries such as tanneries, textile dyeing, battery recycling, and metal processing discharge effluents containing hazardous toxicants, particularly heavy metals like lead (Pb), cadmium (Cd), arsenic (As), chromium (Cr), and mercury (Hg). These substances have been found across environmental media -including air, water, soil, and food- posing serious health risks, especially for children, pregnant women, and industrial workers. Materials and Method: This systematic review was conducted following PRISMA guidelines. A total of 35 peer-reviewed studies published between 2009 and 2024 were selected from electronic databases. Studies were included if they assessed heavy metal concentrations, exposure pathways, health effects, or ecological impacts in industrial areas of Bangladesh. Data extraction included study location, sample type, toxicant concentration, health endpoints, and risk metrics such as Hazard Index (HI) and Target Carcinogenic Risk (TCR). Geographic coverage spanned major industrial hubs including Dhaka, Gazipur, Narayanganj, Savar, Hazaribagh, Kushtia, Tangail, and Sylhet. Results: The review revealed heavy metal contamination in street dust, vegetables, rice, water, and biological samples. Blood lead levels among battery workers averaged 65.25 µg/dL, far exceeding safe limits. Arsenic in drinking water reached up to 0.146 mg/L, over 14 times the World Health Organization (WHO) guideline. Children near industrial zones had elevated urinary metal levels associated with neurodevelopmental issues. Environmental impacts included degraded soil fertility, disrupted aquatic ecosystems, contaminated groundwater, and food chain bioaccumulation. Conclusion: Industrial toxicants pose a critical and often underestimated public health and ecological threat in Bangladesh. Urgent, coordinated policy action is needed to strengthen pollution control, enforce effluent treatment, enhance occupational safety, and expand environmental surveillance and public health education. J Med Coll Women Hosp.2025; 21 (2):175-191